Conditional relative survival among patients with chronic lymphocytic leukaemia: A population‐based study in the Netherlands. Issue 1 (20th December 2021) - van der Straten, Lina; Levin, Mark‐David; Visser, Otto; Posthuma, Eduardus F.M.; Doorduijn, Jeanette K.; Kater, Arnon P.; Dinmohamed, Avinash G.
Abstract: Studies on conditional relative survival (CRS) in chronic lymphocytic leukaemia (CLL) have hitherto been lacking in the literature. We predicted up‐to‐date estimates of 5‐year RS at diagnosis and for each additional year survived (i.e., CRS) up to 15 years post‐diagnosis among CLL patients diagnosed during 2007–2020. We showed that 5‐year CRS continues to decline gradually with each additional year survived in a contemporary era with access to novel‐based agents, irrespective of age. This finding indicates that CLL patients continue to experience substantial excess mortality compared to an age‐ and sex‐matched group from the general population.